2021
DOI: 10.3390/polym13101597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Styrene-Butadiene Based Thermoplastic Magnetorheological Elastomers with Surface-Treated Iron Particles

Abstract: Magnetorheological elastomers (MRE) are increasing in popularity in many applications because of their ability to change stiffness by applying a magnetic field. Instead of liquid-based 1 K and 2 K silicone, thermoplastic elastomers (TPE), based on styrene-butadiene-styrene block copolymers, have been investigated as matrix material. Three different carbonyl iron particles (CIPs) with different surface treatments were used as magneto active filler material. For the sample fabrication, the thermoplastic pressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Studies employing SEBS as matrix with CI microparticles have reported an MR effect of around 5% for volume fractions of 10% 39 . Hence, the MR effect presented in this work is outstanding, not just for the MR response per se, but also for the fact of obtaining this response with NPs with lower saturation magnetization 38 and much smaller percentage.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Studies employing SEBS as matrix with CI microparticles have reported an MR effect of around 5% for volume fractions of 10% 39 . Hence, the MR effect presented in this work is outstanding, not just for the MR response per se, but also for the fact of obtaining this response with NPs with lower saturation magnetization 38 and much smaller percentage.…”
Section: Resultsmentioning
confidence: 63%
“…Studies employing SEBS as matrix with CI microparticles have reported an MR effect of around 5% for volume fractions of 10%. 39 Hence, the MR effect presented in this work is outstanding, not just for the MR response per se, but also for the fact of obtaining this response with NPs with lower saturation magnetization 38 and much smaller percentage. The improve MR response is attributed to the weaker dipolar magnetic interaction between the particles, leading the SEBS matrix to a lower interfacial stress in the surroundings of those magnetic inclusions, which is a determining factor in the performance of these composites.…”
Section: Magnetorheological Propertiesmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, the magnitude of the MR effect has been determined as the percentage change in the storage modulus of the sample with and without the applied maximum magnetic field: MR effect ( % ) = G ( H = 775 mT ) G ( H = 0 ) G ( H = 0 ) × 100 …”
Section: Resultsmentioning
confidence: 99%